Decomposição da desigualdade salarial no Brasil - Silveira, Felipe de Jesus Macedo (2012)
This paper investigates what happened with wage inequality in Brazil from 1981 to 2009. We used four observable characteristics: edcuation, experience, the economic activity that the individual works and the region where he lives. The e ects of these characteristics are estimated by RIF regressions. The advantage of this method is that we can divide distributional changes into a wage structure e ect and a composition e ect and further divide the two components into contribution of each explanatory variable. We nd that the wage inequality in Brazil declines signi cantly from the late 1990 and this is explained mainly by a change in the returns of education.